2007
DOI: 10.1161/strokeaha.106.481465
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and Death After Hospitalization for Acute Ischemic Stroke

Abstract: Background and Purpose-Stroke is a leading cause of hospital admission among the elderly. Although studies have examined subsequent vascular outcomes, limited data are available regarding the full burden of hospital readmission after stroke. We sought to determine the rates of hospital readmissions and mortality and the reasons for readmission over a 5-year period after stroke. Methods-This retrospective observational cohort study included Medicare beneficiaries aged Ͼ65 years who survived hospitalization for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
137
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 38 publications
15
137
1
2
Order By: Relevance
“…There is scant information on stroke recurrence in Norway, but our rate is low compared to many large international incidence studies (Bravata, Ho, Meehan, Brass, & Concato, 2007; Lovett et al, 2004; Sacco et al, 1994; Smith, Frytak, Liou, & Finch, 2005). Most of these studies included patients dating several decades back.…”
Section: Discussionmentioning
confidence: 83%
“…There is scant information on stroke recurrence in Norway, but our rate is low compared to many large international incidence studies (Bravata, Ho, Meehan, Brass, & Concato, 2007; Lovett et al, 2004; Sacco et al, 1994; Smith, Frytak, Liou, & Finch, 2005). Most of these studies included patients dating several decades back.…”
Section: Discussionmentioning
confidence: 83%
“…Among the 304 readmissions, the median (IQR) time to readmission was 11 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) days. The most common readmission diagnoses by CCS Level 3 category were congestive heart failure, pneumonia, coronary atherosclerosis without acute myocardial infarction, cardiac dysrhythmias, and obstructive chronic bronchitis, which together accounted for 25 % of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…Among all hospitalized Medicare beneficiaries (including community-dwelling and institutionalized elders, as well as younger disabled Medicare beneficiaries), nearly one in five were readmitted within 30 days, and over one-third were readmitted within 90 days. 1 These readmitted individuals have been described in some detail; research has identified early readmission risk factors for general 2,3 and geriatric populations, [4][5][6] as well as those with specific diseases such as heart failure, 7 stroke, 8 and chronic obstructive pulmonary disease. 9 Individuals readmitted early are more likely to have multiple medical comorbidities, greater length of stay during the index hospitalization, and additional recent hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the highest rates of readmission are shown to be among those with heart failure, pneumonia and chronic obstructive pulmonary disease (COPD) conditions at discharge [9] . Bravata and colleagues report high rates of readmissions for stroke patients [16] . Another study found that heart attack, pneumonia, and congestive heart failure are three key diagnoses that require special attention due to higher than average readmission rates [17] .…”
Section: Introductionmentioning
confidence: 99%